2019
DOI: 10.1039/c8tc05554h
|View full text |Cite
|
Sign up to set email alerts
|

Band gap and band alignment prediction of nitride-based semiconductors using machine learning

Abstract: Nitride has been drawing much attention due to its wide range of applications in optoelectronics and remains plenty of room for materials design and discovery. Here, a large set of nitrides have been designed, with their band gap and alignment being studied by first-principles calculations combined with machine learning. Band gap and band offset against wurtzite GaN accurately calculated by the combination of screened hybrid functional of HSE and DFT-PBE were used to train and test machine learning models. Aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 33 publications
(36 reference statements)
0
44
0
Order By: Relevance
“…To better validate the accuracy of proposed empirical pseudopotential method inbuilt in FullBand simulator 15 , used for the full band structure simulation in current manuscript, the authors have compared and contrasted the energy values at gamma valley with previously reported experimental data taken from references 5 , 7 , 23 27 . Band gaps for AlN, GaN, InN, and Al 0.2 Ga 0.8 N, In 0.2 Al 0.8 N and In 0.2 Ga 0.8 N alloys are also compared with the results obtained by various density functional theories including LDA 5 , 7 , 28 , LDA-1/2 5 , PBE 7 , 12 , 28 and HSE 7 , 12 , 28 methods. All the comparison data are tabulated in Table 3 .…”
Section: Numerical Techniquementioning
confidence: 99%
See 4 more Smart Citations
“…To better validate the accuracy of proposed empirical pseudopotential method inbuilt in FullBand simulator 15 , used for the full band structure simulation in current manuscript, the authors have compared and contrasted the energy values at gamma valley with previously reported experimental data taken from references 5 , 7 , 23 27 . Band gaps for AlN, GaN, InN, and Al 0.2 Ga 0.8 N, In 0.2 Al 0.8 N and In 0.2 Ga 0.8 N alloys are also compared with the results obtained by various density functional theories including LDA 5 , 7 , 28 , LDA-1/2 5 , PBE 7 , 12 , 28 and HSE 7 , 12 , 28 methods. All the comparison data are tabulated in Table 3 .…”
Section: Numerical Techniquementioning
confidence: 99%
“…LDA local density approximation, LDA-1/2 approximately includes the self-energy of excitations in semiconductors, PBE Perdew–Burke–Ernzerhof (PBE) exchange energy theory, HSE Heyd–Scuseria–Ernzerhof exchange–correlation functional uses an error function screened Coulomb potential to calculate the exchange portion of the energy. *calculated from modified Vegard’s law 11 , 12 where A and B represent band gap values for binary nitride alloys and b is bowing parameter 12 .…”
Section: Numerical Techniquementioning
confidence: 99%
See 3 more Smart Citations